UPAYA LANSIA DALAM MENJAGA KESEIMBANGAN TUBUH DI PANTI SOSIAL LANJUT USIA HARAPAN KITA PALEMBANG - Fera Siska (Jurnal Kesehatan dan Pembangunan, 2023)
Elderly is a group of people aged 60 years and over. This type of research uses a qualitative method with a phenomenological study approach, namely to explore the efforts of the elderly in maintaining body balance at the Harapan Kita Social Institution for the Elderly in Palembang. Research results The results of interviews and observations on Mrs "A" found that Mrs "A" experienced a balance disorder because Mrs "A" experienced several changes such as her vision began to blur, her hearing began to decrease, her muscles became weak, and also Mrs "A" had history of rheumatic disease in both leg joints. To maintain her balance when walking, Mrs "A" always uses a cane. Mrs "A" also always uses sandals when walking, maintains an adequate sleep pattern, namely 2 hours of naps and 8 hours of sleep at night, and the results of interviews and observations on Mrs "S" found that Mrs "S" experienced balance disorders because Mrs " S” experienced several changes, such as his vision began to blur, his hearing began to decline, his muscles became weak, and Mrs. “S” also had a history of osteoarthritis. To maintain her body balance, Mrs "S" always maintains a healthy diet by consuming whole grains and nuts, consuming more fruits and vegetables and consuming low-fat milk, reducing salt and sweet drinks. For her activities Mrs "S" always wears sandals when walking and uses a cane. It is suggested to health workers to increase counseling about maintaining body balance in the elderly so that the elderly can improve their body balance.